Accurate CMOS-based Current Conveyors - Surakampontorn, Wanlop; Riewruja, Vanchai; Kumwachara, Kiattisak; Dejhan, Kobchai (My University, 1991)
An integrable circuit technique for implementing both positive and negative second generation current conveyors (CCII) is described in this paper. The realization method is suitable for fabricating in CMOS technology. The performance of the CMOS-based CCIIs is discussed in detail. Simulation and experimental results are also included. © 1991 IEEE